2021
DOI: 10.1042/bst20200672
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal complications associated with pathological iron toxicity and its molecular mechanisms

Abstract: Iron is fundamental for several biological functions, but when in excess can lead to the development of toxic events. Some tissues and cells are more susceptible than others, but systemic iron levels can be controlled by treating patients with iron-chelating molecules and phlebotomy. An early diagnostic can be decisive to limit the progression of musculoskeletal complications like osteoarthritis and osteoporosis because of iron toxicity. In iron-related osteoarthritis, aggravation can be associated to a few ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 137 publications
0
14
0
Order By: Relevance
“…It is known that articular cartilage damage is the most obvious pathologic feature leading to joint dysfunction. Earlier research reported several ferroptosis‐related features, such as abnormal iron metabolism, 10 , 11 , 37 , 38 lipid peroxidation 39 , 40 and mitochondrial dysfunction, 41 , 42 are closely correlated with accelerating cartilage destruction. It is only recently that Yao et al 9 first demonstrated that chondrocyte ferroptosis contributes to the progression of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that articular cartilage damage is the most obvious pathologic feature leading to joint dysfunction. Earlier research reported several ferroptosis‐related features, such as abnormal iron metabolism, 10 , 11 , 37 , 38 lipid peroxidation 39 , 40 and mitochondrial dysfunction, 41 , 42 are closely correlated with accelerating cartilage destruction. It is only recently that Yao et al 9 first demonstrated that chondrocyte ferroptosis contributes to the progression of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The condition of iron overload is frequently associated with the osteoarthritic phenotypes (such as progressive cartilage erosion, altered subchondral bone microarchitecture, and biomechanics, persistent joint inflammation, proliferative synovitis, and synovial pannus) (Heiland et al, 2010;Simão et al, 2019). Evidence from clinical studies and animal models suggests that iron overload is associated with OA (Husar-Memmer et al, 2014;Kiely, 2018;Simão and Cancela, 2021). At present, iron chelators can be used in the field of first-line therapeutic therapy to eliminate iron overload in vital organs, and osteochondral tissue, and synovium (Rao, 2013;Jansová and Šimůnek, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload is also associated with OA of the joints in patients suffering from diseases associated with iron overload (such as hereditary hemochromatosis (HH), thalassemia, hemophilia, sickle cell disease (SCD)). Iron overload can also result in aging and estrogen deficiency (Dallos et al, 2013;Chehade and Adams, 2019;Simão and Cancela, 2021). HH is the leading case of primary iron overload (Powell et al, 2005), while secondary iron overload is usually caused by the introduction of excess iron in the body.…”
Section: Introductionmentioning
confidence: 99%
“…The role of ferroptosis in musculoskeletal diseases has been well documented [ 50 ]. Ferroptosis in chondrocytes leads to progression of osteoarthritis, which can be alleviated by inhibiting chondrocyte ferroptosis [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%